Malignant Mixed Müllerian Tumor of the Ovary: Clinicopathologic Characteristics, Treatment and Outcome (Annals of Medical Research, 2021)
None
Keywords: Malignant mixed mullerian tumor of the ovary, Treatment, Prognosis